STABILITY OF DEVELOPMENT OF FUTURE PROFESSIONALS’ EMOTIONAL INTELLIGENCE - A. M. Beloborodov; E. E. Symaniuk (Образование и наука)
Introduction. Considerable changes in the world of professions, the intensity of production and consumption of new knowledge, strengthening of a communicative component of professional activity are characteristic features of post-industrial society. Workers who have such professional and psychological qualities as self-control, psychological self-control and ability to operate own emotions and emotions of people around (partners and colleagues) are more in demand in labour market. In this regard, the problem of emotional competency formation of future experts is becoming topical in the system of vocational training.The aim of this paper is to generalize the results of the study on the sustainable development of student emotional intelligence by means of active forms of education (training sessions and workshops).Methodology and research methods. The research methodology is based on the model concept of “Emotional Intelligence” developed by D. V. Lyusin. During the experiment, the method of D. V. Lyusin’s questionnaire EmIn (Emotional Intelligence), D. P. Gilford’s Social Intelligence Test and also the authors’ set of toolkits (tasks for recognition of facial expression and detection of the active dictionary of emotions) were applied.Results and scientific novelty. The authors proved the importance of the high level of emotional intelligence for the modern person irrespective of the sphere of professional employment. The main zones of this type of intelligence and their structural components which should be developed in future experts were highlighted. Features and conditions of formation of practical and academic intelligence were designated. Having tested the hypothesis, it was revealed that social and psychological training is aimed at promoting the acquisition and development of practical intelligence; workshop sessions contribute to academic intelligence. According to hypothetical statements, the authors have developed two options for the experimental course included in the schedule of student’s groups (similar in characteristics) of Ural Federal University (Yekaterinburg). Results of both forms of training (training sessions and workshops) have confirmed the validity of the assumptions made. To clarify the degree of stability of purposefully created emotional intelligence, repeated diagnostics of the competencies mastered by students was carried out one and a half years after. The comparative analysis of outcome indicators of the forming experiment and the revealed residual knowledge and skills has shown not only firmness of psychological changes in students in the field of emotional competency, but also the start of mechanisms of its self-development.Practical significance. Contrary to the opinions of a number of scientists that the emotional intelligence does not change significantly through studentship as main development comes to the end during the teenage period, the authors have proved potential opportunities of increase in the level of emotional competency in the higher education institution. Materials of the research offer prospects for detailed studying of the mechanisms which start and support steady self-development of the emotional intelligence of future experts to provide their continuing competitiveness in rapidly changing social and economic realities.